Attention effect on student's creative self-efficacy and the role of gender. (September 2021) - Gajda, Aleksandra; Gralewski, Jacek
Abstract: The aim of this study was to investigate the relationship between the functioning of students' attention, their creative abilities and creative self-efficacy in math and language depending on their gender. The study included a randomly selected sample of 523 middle school students (53.2% girls and 46.8% boys). The results of the study show that focus of attention is a significant predictor of creative self-efficacy in the case of girls, but not among boys, while fluency of thinking is an important predictor of creative self-efficacy only in the group of boys. The results of the study are discussed in the light of research on the relationships between focus of attention and creative performance and the differences in the socialisation of girls and boys.